2020
DOI: 10.1177/2049463720920760
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of predictors of the disengagement of the descending inhibitory pain modulation system in fibromyalgia: an exploratory study

Abstract: Background: The main symptoms of fibromyalgia comprise diffuse pain, disability, depressive symptoms, catastrophizing, sleep disruption and fatigue, associated with dysfunction of the descending pain-modulating system (DPMS). Objectives: We aimed to identify patterns of main symptoms of fibromyalgia and neuroplasticity biomarkers (i.e. brain-derived neurotrophic factor (BDNF) and S100B protein) in non-responders to the conditioned pain modulation task (CPM-task) induced by immersion of hand in cold water (0–1°… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 74 publications
3
20
0
Order By: Relevance
“…Thus, these areas’ hyper-connectivity suggests that the FC may be a marker of cortical network reorganization, and it highlights that this cortical restructuring is associated with DPMS dysfunction. These functional changes may also be processes underpinning central sensitization’s pathophysiology, integrating cortical brain networks’ deterioration with the corticospinal pain pathways [60]. Consistent with our findings of increased FC in DPMS dysfunction, earlier fMRI studies found that in patients with chronic pain, including chronic low back pain and fibromyalgia, the increased FC between the insula cortex and default mode network, including the medial PFC, is correlated with pain perception intensity [11, 39, 42].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, these areas’ hyper-connectivity suggests that the FC may be a marker of cortical network reorganization, and it highlights that this cortical restructuring is associated with DPMS dysfunction. These functional changes may also be processes underpinning central sensitization’s pathophysiology, integrating cortical brain networks’ deterioration with the corticospinal pain pathways [60]. Consistent with our findings of increased FC in DPMS dysfunction, earlier fMRI studies found that in patients with chronic pain, including chronic low back pain and fibromyalgia, the increased FC between the insula cortex and default mode network, including the medial PFC, is correlated with pain perception intensity [11, 39, 42].…”
Section: Discussionmentioning
confidence: 99%
“…We conducted this study to test whether FC by fNIRS in fibromyalgia patients might constitute a biomarker of the DPMS dysfunction assessed by the CPM-test, evaluated according to changes in the Numerical Pain Scale (NPS) (0-10 points) during the immersion of the dominant hand in cold water [60]. Therefore, we have compared the FC of bilateral MC and PFC between groups of CPM-test responders and nonresponders in female fibromyalgia patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, the difference between the NPS 0-10 at the start of the test (T0) and the pain score on the NPS (0-10) during the cold-water immersion (QST + CPM-test) at the temperature set at 6/10 during T1 was used to determine the CPM-test score. Responders would have values lower than zero whereas non-responders would have a difference in the count on NPS (T1 T0) equal to zero or higher (Botelho et al, 2016;Soldatelli et al, 2021). (f) Pain pressure threshold (PPT): To conduct the test, we employed an electronic algometer from J-Tech Medical Industries in Midvale, Utah, United States.…”
Section: Evaluation Of the Independent Variablesmentioning
confidence: 99%
“…In several musculoskeletal chronic pain diseases, such as myofascial pain syndrome, FM, and osteoarthritis, the intensity of descending pain inhibitory system (DPIS) dysfunction is connected to pain severity ( Botelho et al, 2016 ; Caumo et al, 2016 ). Additionally, serum brain-derived neurotrophic factor (BDNF) levels have a positive correlation with the degree of DPMS dysfunction ( Soldatelli et al, 2021 ). According to Ong et al (2019) , this neurotrophic factor is highly expressed in the PFC in chronic pain and is a crucial marker of neuroplasticity linked to structural changes in various cortical regions responsible for learning, memory, fear, and emotional responses (such as the hippocampus and amygdala) ( Mazza et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%